(untitled) (The Review of Diabetic Studies, 2025)
Background Medical device technology has evolved from rudimentary tools to sophisticated systems integrating AI, IoMT, nanotechnology, and robotics, revolutionizing diagnosis, treatment, and monitoring across clinical domains.​ Methods This comprehensive review synthesizes recent literature on advances in device categories (diagnostic, therapeutic, monitoring, implantable), emerging technologies, regulatory frameworks, clinical impacts, challenges, and future directions through historical analysis, classification overviews, and case studies from regulatory databases and clinical trials.​ Results Key findings highlight innovations like AI-enhanced imaging, wearable biosensors, 3D-printed implants, and precision therapies improving outcomes in cardiology, oncology, and neurology, alongside challenges in biocompatibility, cybersecurity, and global accessibility.​ Conclusions Emerging trends promise personalized, predictive healthcare via integrated technologies, necessitating enhanced regulatory harmonization, cross-disciplinary collaboration, and equitable access to maximize clinical benefits and safety.​